Neuroscience for dentistry - O'Kane, Barbara J. (Thieme, 2022)
A practical, reader-friendly guide for dental students on the neuroscience of the orofacial region Understanding neural mechanisms that control orofacial pain, proper masticatory function, taste, speech, swallowing, and proprioceptive input to the temporomandibular joint and teeth is an important facet of dentistry. Neuroscience of Dentistry by renowned educators Barbara J. O'Kane and Laura C. Barritt provides foundational knowledge on these topics. The tex.